Saucer - Coonts, Stephen (St. Martin's Griffin, 2002)
When Rip Cantrell, a seismic survey worker in the Sahara, spots a glint of reflected light in the distance, he investigates-and finds a piece of metal apparently entombed in the sandstone. Before long, Rip and his colleagues uncover a flying saucer that has been resting there for 140,000 years.
Keywords: Adventure fiction; Science fiction; Americans; Space flight; Unidentified flying objects